Signals from the deep-sea: Genetic structure, morphometric analysis, and ecological implications of Cyclothone braueri (Pisces, Gonostomatidae) early life stages in the Central Mediterranean Sea. (July 2021) - Torri, Marco; Pappalardo, Anna Maria; Ferrito, Venera; Giannì, Salvatore; Armeri, Grazia Maria; Patti, Carlo; Mangiaracina, Francesca; Biondo, Girolama; Di Natale, Marilena; Musco, Marianna; Masullo, Tiziana; Bennici, Carmelo; et al.
Abstract: Cyclothone braueri (Stomiiformes, Gonostomatidae) is a widely distributed fish inhabiting the mesopelagic zone of marine tropical and temperate waters. Constituting one of the largest biomasses of the ocean, C. braueri is a key element in most of the ecological processes occurring in the twilight layer. We focused on the ecological processes linked to early life stages in relation to marine pelagic environmental drivers (temperature, salinity, food availability and geostrophic currents) considering different regions of the Central Mediterranean Sea. A multivariate morphometric analysis was carried out using six parameters with the aim of discerning different larval morphotypes, while a fragment of 367 bp representing the 12S ribosomal RNA gene was used to perform molecular analyses aimed at determining the intraspecific genetic variability. Analysis highlighted two geographically distinct morphotypes not genetically discernible and related to the different nutritional conditions due to spatial heterogeneities in terms of temperature and food availability. The body depth (BD) emerged as an appropriate morphometric parameter to detect the larval condition in this species. Molecular analysis highlighted a moderate genetic divergence in the fish population, showing the recurrence of two phylogroups not geographically separated. Highlights: Two larval morphotypes not genetically discernible were found in the regions. Larval morphotypes were related to temperature and trophic conditions. The body diameter emerged as an appropriate parameter to detect the larval condition. Molecular analysis evidenced not geographically separated haplogroups.